Grammar of the ugaritic language. - Sivan, Daniel (Brill, 2001)
Ugaritic, discovered in 1929, is a North-West Semitic language, documented on clay tablets (about 1250 texts) and dated from the period between the 14th and the 12th centuries BCE. This text deals with the phonology, morphology and syntax of Ugaritic.